IMPLEMENTATION THEMATIC STUDENT STUDY SERVICE FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITAS PASUNDAN DURING COVID 19 PANDEMIC - Taufiqulloh Dahlan; Uus Toharudin; Darta Darta; Acep Roni Hamdani; Rahmatika Rahmatika (LPM Universitas Pasundan, 2022)
The Covid-19 pandemic is still something that worries everyone. The Covid-19 outbreak has made everyone cannot carry out activities both in the fields of education, society, and Village government. In Indonesia itself, there have been large restrictions on activities namely PSBB and PPKM. This research activity was carried out during PPKM conditions. The students try continue to serve in the fields of education, community, and village government. College student What is done in terms of education is to provide online learning assistance and activities other. While in the social community service is carried out by counseling or work devotion. And the last service in the field of village government is helping the village in run village programs. By providing learning assistance, students can produce good study quality. While in community service, realizing how to live live healthy during the current pandemic. The village government is helped by the service that is done by assisting in carrying out village programs. The thematic student study service work program that has been planned can run well even though there are some activities that have been changed due to several obstacles in the field. Forming students to be more mature in responding to existing problems and being able to understand how to live in society, besides that they can form independent personalities and are responsible for the tasks that must be carried out. Students gain new knowledge that is not found in the material in class that is useful later for use in everyday life. The local government and the community were enthusiastic and very helpful in the implementation of the Thematic Community Service Program. This thematic student study service activity is a student service effort to the community.